2017
DOI: 10.1016/j.ymthe.2017.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Antigen and Receptor Densities Regulate Efficacy of a Chimeric Antigen Receptor Targeting Anaplastic Lymphoma Kinase

Abstract: We explored the utility of targeting anaplastic lymphoma kinase (ALK), a cell surface receptor overexpressed on pediatric solid tumors, using chimeric antigen receptor (CAR)-based immunotherapy. T cells expressing a CAR incorporating the single-chain variable fragment sequence of the ALK48 mAb linked to a 4-1BB-CD3ζ signaling domain lysed ALK-expressing tumor lines and produced interferon-gamma upon antigen stimulation but had limited anti-tumor efficacy in two xenograft models of human neuroblastoma. Further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
268
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 293 publications
(290 citation statements)
references
References 65 publications
(87 reference statements)
19
268
1
2
Order By: Relevance
“…For example, with anti-CD22 CAR T cell therapy, a simple quantitative decrease in CD22 cell surface expression or antigen density in the leukaemic population was adequate to evade the CAR T cells, thus enabling leukaemic relapse despite ongoing CD22 positivity, with individual variation seen in the threshold antigen density that conferred relapse or resistance 15 . Notwithstanding, a minimum threshold of antigen expression is likely to be needed for functional and/or preserved CAR T cell activity -a concept that has been realized in preclinical models with targeting of both CD20 in B cell malignancies 117 and ALK in neuroblastoma 118 , in which CAR T cell cytolytic activity and cytokine production were increased with higher levels of antigen expression. Along these lines, preclinical experience with an EGFR-targeted CAR T cell therapy suggests therapeutic potential that relies specifically on the differential antigen density of EGFR in tumours versus nonmalignant tissues to limit on-target, off-tumour toxicities while maintaining anticancer activity 119 .…”
Section: Antigen Loss or Modulation As A Mechanism Of Immune Escapementioning
confidence: 99%
See 1 more Smart Citation
“…For example, with anti-CD22 CAR T cell therapy, a simple quantitative decrease in CD22 cell surface expression or antigen density in the leukaemic population was adequate to evade the CAR T cells, thus enabling leukaemic relapse despite ongoing CD22 positivity, with individual variation seen in the threshold antigen density that conferred relapse or resistance 15 . Notwithstanding, a minimum threshold of antigen expression is likely to be needed for functional and/or preserved CAR T cell activity -a concept that has been realized in preclinical models with targeting of both CD20 in B cell malignancies 117 and ALK in neuroblastoma 118 , in which CAR T cell cytolytic activity and cytokine production were increased with higher levels of antigen expression. Along these lines, preclinical experience with an EGFR-targeted CAR T cell therapy suggests therapeutic potential that relies specifically on the differential antigen density of EGFR in tumours versus nonmalignant tissues to limit on-target, off-tumour toxicities while maintaining anticancer activity 119 .…”
Section: Antigen Loss or Modulation As A Mechanism Of Immune Escapementioning
confidence: 99%
“…One key issue with solid tumours is that the inherent tumour heterogeneity is likely to be a substantial barrier to identifying an optimal target, and relatedly, antigen loss will probably be a key factor precluding curative remissions. Indeed, antigen density (as mentioned above regarding ALK in neuroblastoma cells 118 ) and inherent tumour heterogeneity in antigen expression in solid tumours (for example, mesothelin 154 , HER2 (ref. 155 ) or MUC1 (ref.…”
Section: Car T Cell Strategies Beyond B Cell Targeting Cd19mentioning
confidence: 99%
“…In the context of CD22-CARs, a comparison between two scFvs targeting the same epitope but with varying affinities did not reveal a significant impact of affinity on CAR function, whereas an alternative CD22 binder (m971) with lower affinity proved most efficacious, possibly because of better accessibility of the targeted epitope 34,35 . Thus, for a given antigen density on a target cell, there is likely to be an optimal range of scFv affinities and CAR expression levels required for a specific and effective antitumor response [36][37][38] .…”
Section: Review Articlementioning
confidence: 99%
“…Although targeting TAAs also expressed on normal tissues risks on-target, off-tumour toxicity, evidence from preclinical models suggests that CAR-T cells may not react to low-level antigen expression in healthy tissues 33,[36][37][38] . Instances of human epidermal growth factor receptor 2 (HER2)-CAR off-tumour toxicity 82 have been largely overshadowed by safe trials with a distinct HER2-CAR that demonstrated clinical efficacy in patients with sarcomas 91,92 .…”
Section: Nature Biomedical Engineeringmentioning
confidence: 99%
“…Both UniCAR and SplitCAR are titratable ''onswitch'' platforms enabling better control of the timing, dosage and activation of CAR T-cells. Beyond tumor-specificity, both antigen and CAR densities of expression at the membrane are likely to contribute to CAR T-cell activation [58]. Low or fluctuating expressions are unlikely to provide strong enough CAR stimulation.…”
Section: Limiting Off-tumor Toxicitymentioning
confidence: 99%